Report on the Sculptured Stones older than A.D. 1100, with Symbols and Celtic Ornament, in the District of Scotland South of the River Dee; obtained under the Victoria Jubilee Gift of His Excellency Dr. R. H. Gunnning, F.S.A. Scot - Allen, John Romilly (Proceedings of the Society of Antiquaries of Scotland, 1892)